2016
DOI: 10.1016/j.dental.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization shrinkage kinetics and shrinkage-stress in dental resin-composites

Abstract: Shrinkage-strainShrinkage-stress Strain rate Modulus of elasticity Bulk-fill a b s t r a c tObjectives. To investigate a set of resin-composites and the effect of their composition on polymerization shrinkage strain and strain kinetics, shrinkage stress and the apparent elastic modulus.Methods. Eighteen commercially available resin-composites were investigated. Three specimens (n = 3) were made per material and light-cured with an LED unit (1200 mW/cm 2 ) for 20 s. The bonded-disk method was used to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
125
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 75 publications
8
125
0
4
Order By: Relevance
“…In addition, all methacrylate-based RCs shrink to some extent, and shrinkage can be reduced by using monomers with a high molecular weight. 29 Higher polymerization shrinkage was observed in FSS, and this can be explained by the application of single-increment RC (4 mm) instead of the incremental filling recommended by the manufacturer (Table 1). Shrinkage in the incremental technique was similar to that of bulk fill RCs, but the incremental filling technique increases the deformation of the restored tooth, which could be a negative outcome due to higher stress on the tooth-composite structure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all methacrylate-based RCs shrink to some extent, and shrinkage can be reduced by using monomers with a high molecular weight. 29 Higher polymerization shrinkage was observed in FSS, and this can be explained by the application of single-increment RC (4 mm) instead of the incremental filling recommended by the manufacturer (Table 1). Shrinkage in the incremental technique was similar to that of bulk fill RCs, but the incremental filling technique increases the deformation of the restored tooth, which could be a negative outcome due to higher stress on the tooth-composite structure.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancies between the polymerization contraction gaps presented by the composites are linked to significant differences in the content of filler particles per volume in the composition of these materials 16 . This factor can be verified in the X-tra Base (Voco) resin, which presented smaller gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a higher presence of Bis-GMA reduces conversion and shrinkage of polymerization, as well as it explains the high viscosity observed by the hydroxyl groups and the rigidity provided by the aromatic rings (high molecular weight) allowing a smaller agglomeration of reactive groups. These factors are responsible for the decrease in the mobility necessary for the dissemination of the polymer chain, thus reducing the final conversion 11 . For all studied resins the presence of UDMA was observed, fact that demonstrates a standardization and possible minimization of the polymerization shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…64 Among the bulk-fill composites with modifications to the organic matrix are addition of low-shrink or higher molecular weight monomers or stress-relieving additives. 65 It was demonstrated that bulk-fill composites had reduced post-gel shrinkage and that restorations with bulk-fill composites had reduced cuspal deformation and shrinkage stress, and that the fracture resistance increased when compared with incrementally filled teeth. 10 Clinically, few trials evaluating restorations with bulk-fill composites are available yet because these materials were only recently introduced.…”
Section: Use Of Bulk Fill Compositementioning
confidence: 99%
“…66,67 It is important to emphasize that differences in strategies adopted by manufactures to obtain bulk-fill composites affect the behavior of these materials regarding depth of polymerization and generation of shrinkage stress and therefore results observed cannot be extrapolated to all materials that are classified by their manufacturer as bulk-fill. 65 Delayed light-activation of dual-cure cements Dual-cure resin cements are largely used to lute indirect restorations or fiber posts because they were designed to provide proper working time and curing, even in the absence of adequate light-activated polymerization. However, these advantages are not fully achieved and dual-cure cements usually require additional light-activation to achieve the desired mechanical properties, conversion, and bond strength.…”
Section: Use Of Bulk Fill Compositementioning
confidence: 99%